A composite catalyst and its preparation method and application

By preparing boron-doped transition metal hydroxyoxide catalyst on a self-supporting substrate, the problems of complexity and cost of preparing multi-stage structural catalysts in the prior art are solved, and the efficient and stable OER electrocatalytic effect in seawater media is achieved. .

CN115161693BInactive Publication Date: 2024-12-27SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210831956.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-15
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art When preparing multi-stage structural transition metal hydroxyoxide catalysts, the method is complex, high cost, long time and harsh reaction conditions, making it difficult to prepare on a large scale under mild conditions, and catalyze the stability and selection of OER in seawater media. Insufficient sex.

Method used

The metal organic frame precursor is prepared on a self-supporting substrate by co-precipitation method, and a multi-stage structure boron-doped transition metal hydroxyoxide catalyst is prepared by annealing and repeated impregnation methods, simplifying the process, reducing costs, and improving catalytic activity and stability. .

Benefits of technology

It is possible to quickly and economically prepare composite catalysts with multi-stage structure and high active specific surface area under mild conditions, significantly improving the OER electrocatalytic activity and stability in seawater media and avoiding electrode corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115161693B_ABST
    Figure CN115161693B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite catalyst and a preparation method and application thereof. The preparation method comprises the following steps: adding a solution A containing a first type of transition metal salt to a solution B containing an organic ligand to obtain a solution C; immersing a self-supporting substrate in the solution C and letting it stand, then taking it out to dry and annealing it to prepare a transition metal oxide on the self-supporting substrate; immersing the self-supporting substrate containing the transition metal oxide on the surface into a solution D containing a second type of transition metal salt and letting it stand, then immersing it into a solution E containing sodium borohydride and a soluble alkali and letting it stand, repeating this step several times to obtain a composite catalyst. The present invention prepares a self-supporting structure composite catalyst having a multi-level structure, uniform morphology, large specific surface area and many active sites by a simple coprecipitation method and a repeated impregnation method. The preparation method of the present invention is short in time consumption, simple in preparation process, simple and mild in reaction conditions, low in cost, environmentally friendly and can be prepared on a large scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a composite catalyst and a preparation method and application thereof. Background Art

[0002] Reducing the cost of hydrogen production by water electrolysis and realizing direct hydrogen production by seawater electrolysis in offshore areas will effectively promote the development of hydrogen energy economy. The oxygen evolution reaction (OER) at the anode end of water electrolysis involves four-electron transfer, and its kinetics are slow, so it is urgent to develop efficient and stable electrocatalysts to reduce the activation energy of the reaction. Ir and Ru-based compounds have high intrinsic activity in catalyzing OER, but their high price limits their large-scale application in industry. In addition, seawater contains a large amount of chloride ions, which are prone to compete with OER and cause electrode corrosion. Therefore, it is urgent to develop low-cost, highly selective and stable OER electrocatalysts to truly realize industrial seawater electrolysis for hydrogen production. Hierarchical transition metal oxyhydroxides have high intrinsic activity in catalyzing OER. Hierarchical structural materials can not only retain the inherent characteristics of the constituent units, but also introduce other structural features, such as providing a larger specific surface area and a developed pore structure. At present, the preparation of transition metal hydroxide catalysts based on multi-level structures is mainly carried out through hydrothermal / solvothermal and hard / soft templates and electrochemical reconstruction. However, the above methods are highly dependent on thermal energy or structure-directing agents (templates, surfactants, etc.) or host material sacrificial methods to induce heterogeneous nucleation / growth and the formation of multi-level structures, which inevitably increases the ecological, economic and time costs. At the same time, the entire reaction conditions in the high-temperature non-aqueous phase system are harsh and relatively complex, which is not conducive to studying the growth process and self-assembly behavior of multi-level transition metal hydroxides. Therefore, it is urgent to develop a simple method for preparing multi-level transition metal hydroxides under mild conditions and explore their application in catalyzing OER in seawater media.

[0003] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a composite catalyst and a preparation method and application thereof, aiming to solve the problems of the existing preparation method being time-consuming, costly, and having harsh and complex reaction conditions.

[0005] The technical solution of the present invention is as follows:

[0006] The first aspect of the present invention provides a method for preparing a composite catalyst, which comprises the steps of:

[0007] Step 1: providing a solution A containing a first type of transition metal salt, a solution B containing an organic ligand, a solution D containing a second type of transition metal salt, and a solution E containing sodium borohydride and a soluble base; adding the solution A to the solution B to obtain a solution C; Step 2: immersing a self-supporting substrate in the solution C, standing for a first preset time, and then annealing, to prepare a transition metal oxide on the self-supporting substrate;

[0008] Step 3, immersing the self-supporting substrate having a transition metal oxide on its surface into the solution D, and leaving it to stand for a second preset time;

[0009] Step 4: immersing the product obtained in step 3 into the solution E and leaving it to stand for a third preset time;

[0010] Step 5: Repeat steps 3 to 4 several times to prepare boron-doped transition metal oxyhydroxide on the surface of the transition metal oxide to obtain the composite catalyst.

[0011] Optionally, the transition metal in the first type of transition metal salt is selected from at least one of cobalt, nickel and iron.

[0012] Optionally, the organic ligand is selected from dimethylimidazole.

[0013] Optionally, the second type of transition metal salt is selected from at least one of iron salts, tungsten salts, nickel salts, cobalt salts and manganese salts.

[0014] Optionally, the soluble alkali is selected from at least one of sodium hydroxide and potassium hydroxide.

[0015] Optionally, the self-supporting substrate is selected from at least one of nickel foam, carbon cloth, and copper foam.

[0016] Optionally, the annealing temperature is 300-500° C., the annealing time is 1-3 hours, and the annealing atmosphere is air.

[0017] Optionally, repeat steps 3 to 4 3 to 12 times.

[0018] The second aspect of the present invention provides a composite catalyst, wherein the composite catalyst is prepared by the method for preparing the composite catalyst as described above.

[0019] The third aspect of the present invention provides a use of the composite catalyst as described above in the electrolysis of water to produce hydrogen.

[0020] Beneficial effects: The present invention prepares a self-supporting metal organic framework (MOF) precursor on a self-supporting substrate by a simple coprecipitation method, and after annealing, obtains its oxide (the oxide derived from MOF, i.e. the above-mentioned transition metal oxide), and further prepares a transition metal hydroxide oxide on the surface of the MOF-derived oxide by repeated impregnation, thereby obtaining a self-supporting composite catalyst with a multi-level structure and uniform morphology. The synthesis method provided by the present invention is time-consuming, simple in preparation process, mild in reaction conditions, low in cost, environmentally friendly, and can be prepared on a large scale; the constructed composite catalyst has a multi-level structure and a uniform and controllable morphology, and the prepared self-supporting composite catalyst has the characteristics of a large active specific surface area, a large number of active sites, and a regular and orderly three-dimensional multi-level structure, and exhibits excellent electrocatalytic activity and stability for OER in seawater medium. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 (a) is a scanning electron microscope image of Co3O4 / NF in Example 1 of the present invention, and (b) is a scanning electron microscope image of Co3O4@B-(W,Fe)OOH / NF in Example 1 of the present invention.

[0022] Figure 2 This is the XRD diagram of Co3O4@B-(W,Fe)OOH / NF in Example 1 of the present invention.

[0023] Figure 3 This is the linear scanning polarization curve of Co3O4@B-(W,Fe)OOH / NF in Example 1 of the present invention.

[0024] Figure 4 This is a graph showing the stability test results of Co3O4@B-(W,Fe)OOH / NF in alkaline seawater in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] The present invention provides a composite catalyst and a preparation method and application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0026] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0027] The embodiment of the present invention provides a method for preparing a composite catalyst, which comprises the steps of:

[0028] Step 1: providing a solution A containing a first type of transition metal salt, a solution B containing an organic ligand, a solution D containing a second type of transition metal salt, and a solution E containing sodium borohydride and a soluble base; adding the solution A to the solution B to obtain a solution C; Step 2: immersing a self-supporting substrate in the solution C, standing for a first preset time, and then annealing, to prepare a transition metal oxide on the self-supporting substrate;

[0029] Step 3, immersing the self-supporting substrate having a transition metal oxide on its surface into the solution D, and leaving it to stand for a second preset time;

[0030] Step 4: immersing the product obtained in step 3 into the solution E and leaving it to stand for a third preset time;

[0031] Step 5: Repeat steps 3 to 4 several times to prepare boron-doped transition metal oxyhydroxide on the surface of the transition metal oxide to obtain the composite catalyst.

[0032] It should be noted that steps 1 to 5 in the present embodiment are only for the convenience of explanation and do not have a specific limiting effect. According to the operation steps of steps 1 to 5, the order thereof is reasonably adjusted and still belongs to the protection scope of the present invention. For example, step 1 involves the provision of different solutions (solution A, solution B, solution C, solution D, solution E), but it is not limited to that all solutions must be provided or prepared first before other steps are performed. It can be provided or prepared before a certain solution is needed, such as providing or preparing solution D after step 2 and before step 3, and then performing step 3 (immersing a self-supporting substrate containing a transition metal oxide on the surface into the solution D, and standing for a second preset time); providing or preparing solution E after step 3 and before step 4, and then performing step 4 (immersing the product obtained in step 3 into the solution E, and standing for a third preset time), of course, solution E can also be provided or prepared between step 2 and step 3.

[0033] In this embodiment, a self-supporting MOF precursor is prepared on a self-supporting substrate by a simple coprecipitation method, and after annealing, its oxide (the oxide derived from MOF, i.e., the above-mentioned transition metal oxide) is obtained. On this basis, a transition metal hydroxide oxide is further prepared on the surface of the MOF-derived oxide by repeated impregnation, thereby obtaining a self-supporting composite catalyst with a multi-level structure and uniform morphology. The synthesis method provided in this embodiment is short in time, simple in preparation process, simple and mild in reaction conditions, low in cost, environmentally friendly and can be prepared on a large scale. The constructed composite catalyst has a multi-level structure and a uniform and controllable morphology; the prepared self-supporting composite catalyst has the characteristics of a large active specific surface area, many active sites, and a regular and orderly three-dimensional multi-level structure, and exhibits excellent electrocatalytic activity and stability for OER in seawater medium. Specifically, in terms of activity, the transition metal hydroxide oxide in the composite catalyst has a high intrinsic activity for OER, and the multi-level structure can provide more active sites. In addition, boron doping can further improve the conductivity of the transition metal hydroxide oxide, thereby improving the electrocatalytic OER activity of the composite catalyst. In terms of stability, on the one hand, the composite catalyst has high activity and can undergo OER reaction at low potential, thus avoiding the chlorine evolution reaction that corrodes the electrode; on the other hand, the composite catalyst has many active sites, and even if some of the active sites are masked in OER, there are still more active sites to participate in the OER reaction.

[0034] In step 1, in one embodiment, the concentration of the first type of transition metal salt in the solution A is 0.03 to 0.1 mol / L. Specifically, the solution A can be obtained by a method including but not limited to adding the first type of transition metal salt to water.

[0035] In one embodiment, the transition metal in the first type of transition metal salt is selected from at least one of cobalt, nickel, and iron, but is not limited thereto. In this embodiment, the transition metal in the first type of transition metal salt can be a single metal such as cobalt, nickel, or iron, the transition metal in the first type of transition metal salt can also be a bimetallic such as nickel-cobalt or nickel-iron, and the transition metal in the first type of transition metal salt can also be a three-component metal such as nickel-cobalt-iron. As an example, when the transition metal in the first type of transition metal salt is selected from cobalt, the first type of transition metal salt is selected from at least one of cobalt nitrate, cobalt chloride, and cobalt sulfate; when the transition metal in the first type of transition metal salt is selected from nickel, the first type of transition metal salt is selected from at least one of nickel nitrate, nickel chloride, and nickel sulfate; when the transition metal in the first type of transition metal salt is selected from nickel-cobalt, the first type of transition metal salt is selected from nickel-cobalt nitrate.

[0036] In one embodiment, the concentration of the organic ligand in the solution B is 0.2-0.8 mol / L. Specifically, the solution B can be obtained by a method including but not limited to adding the organic ligand into water.

[0037] In one embodiment, the organic ligand includes but is not limited to dimethylimidazole.

[0038] In one embodiment, the solution A is added to the solution B under stirring to obtain a solution C. In this embodiment, the first type of transition metal salt in solution A and the organic ligand in solution B form a MOF precursor.

[0039] In one embodiment, the second type of transition metal salt is selected from at least one of iron salts, tungsten salts, nickel salts, cobalt salts, and manganese salts, but is not limited thereto. As an example, in this embodiment, the second type of transition metal salt can be selected from iron salts, tungsten salts, nickel salts, cobalt salts, or manganese salts; the second type of transition metal salt can also be selected from a mixture of iron salts and tungsten salts, a mixture of iron salts and nickel salts, a mixture of tungsten salts and cobalt salts, a mixture of cobalt salts and manganese salts, etc.; the second type of transition metal salt can also be selected from a mixture of iron salts, tungsten salts, and nickel salts, a mixture of tungsten salts, nickel salts, and cobalt salts, etc. Further, the iron salt is selected from at least one of iron nitrate, iron chloride, and iron sulfate, the tungsten salt is selected from ammonium tungstate or sodium tungstate, the nickel salt is selected from at least one of nickel nitrate, nickel chloride, and nickel sulfate, the cobalt salt is selected from at least one of cobalt nitrate, cobalt chloride, and cobalt sulfate, and the manganese salt is selected from at least one of manganese nitrate, manganese chloride, and manganese sulfate.

[0040] In one embodiment, in the solution D, the concentration of the second type of transition metal salt is 0.1 to 0.3 mol / L. In this embodiment, if the second type of transition metal salt is selected from two or three salts, the total concentration of all salts is 0.1 to 0.3 mol / L. For example, when the second type of transition metal salt is selected from iron salts and tungsten salts, the total concentration of the iron salts and tungsten salts is 0.1 to 0.3 mol / L, wherein the concentration ratio of the iron salt to the tungsten salt can be (0 to 1): 1. Specifically, the solution D can be obtained by including but not limited to adding the second type of transition metal salt to water.

[0041] In one embodiment, in the solution E, the concentration of sodium borohydride is 0.25-0.5 mol / L, and the concentration of the soluble alkali solution is 0.05-0.2 mol / L. Specifically, the solution E can be obtained by including but not limited to adding sodium borohydride and a soluble alkali into water.

[0042] In one embodiment, the soluble base is selected from at least one of sodium hydroxide and potassium hydroxide, but is not limited thereto.

[0043] In step 2, the self-supporting substrate is immersed in the solution C and allowed to stand for a first preset time, a metal organic framework material is prepared on the surface of the self-supporting substrate, and after drying, annealing is performed, and the metal ions in the metal organic framework material are converted into transition metal oxides (oxides derived from MOF), while the organic part is converted into gases such as carbon dioxide and volatilized, and a transition metal oxide is prepared on the self-supporting substrate. The first preset time can be set according to actual needs, for example, it can be 0.5 to 5 hours, and further, it can be 1 to 3 hours.

[0044] In one embodiment, the annealing temperature is 300-500°C, the annealing time is 1-3 hours, and the annealing atmosphere is air. Specifically, the annealing is performed in a tube furnace, and the heating rate is set to 2-5°C·min -1 .

[0045] In one embodiment, the self-supporting substrate is selected from at least one of nickel foam, carbon cloth, and copper foam, but is not limited thereto.

[0046] In step 3, in a further embodiment, the self-supporting substrate having a transition metal oxide on its surface is immersed in the solution D and allowed to stand for a second preset time, so that the second type of transition metal salt in the solution D is loaded on the surface of the transition metal oxide on the surface of the self-supporting substrate. The second preset time can be set according to actual needs, for example, it can be 1 to 20 seconds, and further, it can be 5 to 15 seconds.

[0047] In step 4, the product obtained in step 3 is immersed in solution E and allowed to stand for a third preset time. Solution E provides an alkaline environment and a boron source for doping, which reacts with a second type of transition metal salt on the surface of the transition metal oxide (the transition metal oxide is supported on a self-supporting substrate) to form a boron-doped transition metal oxyhydroxide. The third preset time can be set according to actual needs, for example, it can be 1 to 20 seconds, and further, it can be 5 to 15 seconds. Boron doping can further improve the conductivity of the transition metal oxyhydroxide and improve the electrocatalytic OER performance of the composite catalyst.

[0048] In step 5, in one embodiment, steps 3 to 4 are repeated 3 to 12 times so that the boron-doped transition metal oxyhydroxide is uniformly and densely loaded on the transition metal oxide.

[0049] The embodiment of the present invention also provides a composite catalyst, wherein the composite catalyst is prepared by the preparation method of the composite catalyst as described above in the embodiment of the present invention. The composite catalyst includes a self-supporting substrate, a transition metal oxide loaded on the surface of the self-supporting substrate, and a boron-doped transition metal oxyhydroxide loaded on the surface of the transition metal oxide. In this embodiment, the composite catalyst has the characteristics of a large active specific surface area, a regular and orderly three-dimensional multi-level structure, and the composite catalyst has a large number of active sites and excellent electrocatalytic OER activity and good stability. Specifically, in terms of activity, the transition metal oxyhydroxide in the composite catalyst has a high intrinsic activity for OER, and the multi-level structure can provide more active sites. In addition, boron doping can further improve the conductivity of the transition metal oxyhydroxide and improve the electrocatalytic OER activity of the composite catalyst. In terms of stability, on the one hand, the composite catalyst has high activity, and the OER reaction can occur at a low potential, which can avoid the chlorine evolution reaction of the corrosive electrode; on the other hand, the composite catalyst has many active sites. Even if some of the active sites are covered in OER, there are still more active sites to participate in the OER reaction.

[0050] In one embodiment, the transition metal oxide may be cobalt tetroxide, nickel oxide, ferric oxide, nickel cobalt oxide, nickel iron oxide, and the like.

[0051] In one embodiment, the boron-doped transition metal oxyhydroxide is selected from at least one of boron-doped iron oxyhydroxide, boron-doped tungsten oxyhydroxide, boron-doped nickel oxyhydroxide, boron-doped cobalt oxyhydroxide, and boron-doped manganese oxyhydroxide. That is to say, the boron-doped transition metal oxyhydroxide can be one boron-doped transition metal oxyhydroxide, two boron-doped transition metal oxyhydroxides, or multiple boron-doped transition metal oxyhydroxides. For example, the boron-doped transition metal oxyhydroxide can be boron-doped iron oxyhydroxide, boron-doped tungsten oxyhydroxide, boron-doped nickel oxyhydroxide, boron-doped cobalt oxyhydroxide, or boron-doped manganese oxyhydroxide; the boron-doped transition metal oxyhydroxide can also be a mixture of boron-doped iron oxyhydroxide and boron-doped tungsten oxyhydroxide, a mixture of boron-doped iron oxyhydroxide and boron-doped nickel oxyhydroxide, a mixture of boron-doped nickel oxyhydroxide and boron-doped cobalt oxyhydroxide, etc.; the boron-doped transition metal oxyhydroxide can also be a mixture of boron-doped iron oxyhydroxide, boron-doped tungsten oxyhydroxide, and boron-doped nickel oxyhydroxide, etc.

[0052] In a further embodiment, the composite catalyst includes a self-supporting substrate, cobalt oxide supported on a surface of the self-supporting substrate, and boron-doped iron oxyhydroxide and boron-doped tungsten oxyhydroxide supported on the surface of the cobalt oxide.

[0053] The present invention also provides an application of the composite catalyst described above in the present invention in the electrolysis of water to produce hydrogen. In one embodiment, the composite catalyst is applied in an electrocatalytic oxygen evolution reaction.

[0054] The following describes it in detail through specific embodiments.

[0055] Example 1

[0056] 2 mmol of cobalt nitrate was added to 40 mL of deionized water and stirred for 10 min to obtain solution A; at the same time, 16 mmol of dimethylimidazole was dissolved in 40 mL of deionized water and stirred for 10 min to obtain solution B;

[0057] Under stirring conditions, solution A was slowly added to solution B, and solution C was obtained after stirring for 5 minutes;

[0058] The cleaned nickel foam (NF) was placed obliquely in a beaker containing solution C, left to stand for 2 h, taken out and washed with deionized water, and then dried at 60 °C under vacuum for 12 h to prepare ZIF-67 on the surface of NF. The obtained product was recorded as ZIF-67 / NF.

[0059] ZIF-67 / NF was annealed in a tube furnace at a temperature of 400 °C and a heating rate of 2 °C min -1 , the holding time is 2h, the gas atmosphere is air, after annealing, Co3O4 is prepared on the surface of NF, and the obtained product is recorded as Co3O4 / NF, and its scanning electron microscope picture is shown as follows Figure 1 As shown in (a), its crystal structure is as follows Figure 2 shown.

[0060] 0.675 mmol of ferric nitrate and 0.075 mmol of ammonium tungstate were dissolved in 5 mL of deionized water to obtain solution D; at the same time, 1.875 mmol of sodium borohydride and 0.5 mmol of sodium hydroxide were dissolved in 5 mL of deionized water to obtain solution E;

[0061] The Co3O4 / NF was soaked in solution D for 10 seconds and then taken out. It was then soaked in solution E for 10 seconds and then taken out. This step was repeated 10 times. B-doped WOOH and B-doped FeOOH were prepared on the surface of Co3O4 in Co3O4 / NF, that is, a composite catalyst with a multi-level structure was obtained, which was recorded as Co3O4@B-(W,Fe)OOH / NF. Its scanning electron microscope image is shown in the figure. Figure 1 As shown in (b), B-doped WOOH and B-doped FeOOH nanosheets are uniformly loaded on the surface of Co3O4, and their crystal phase structures are shown in Figure 2 shown.

[0062] The electrochemical tests were performed on a CHI 760E electrochemical workstation. The prepared Co3O4@B-(W,Fe)OOH / NF was selected as the working electrode (area 0.5 cm 2 ), carbon rod as counter electrode, mercury / mercuric oxide electrode as reference electrode, forming a three-electrode system, respectively at 1 mol·L -1 KOH solution, simulated seawater (1 mol·L -1 KOH+0.5mol·L - 1 NaCl) and alkaline seawater (1 mol·L -1 KOH + seawater, that is, the dissolved concentration of seawater is 1 mol·L -1 Electrochemical tests were performed in KOH at 5 mV·s -1 The linear scanning polarization curve test was carried out at a scanning rate of 1.5 ℃. The test results are shown in the attached Figure 3 As shown, in alkaline seawater (1 mol·L -1 The stability test in KOH+seawater is shown in the attached Figure 4 As shown, the results show good stability.

[0063] In summary, the present invention provides a composite catalyst and its preparation method and application. The present invention prepares a self-supporting structure precursor on a self-supporting substrate by a simple coprecipitation method, and obtains its oxide (the oxide derived from MOF, i.e. the above-mentioned transition metal oxide) after annealing. On this basis, a transition metal hydroxide oxide is further prepared on the surface of the MOF-derived oxide by repeated impregnation, thereby obtaining a self-supporting structure composite catalyst with a multi-level structure and uniform morphology. The synthesis method provided in this embodiment is short in time, simple in preparation process, simple and mild in reaction conditions, low in cost, environmentally friendly and can be prepared on a large scale. The constructed composite catalyst has a multi-level structure and a uniform and controllable morphology; the prepared self-supporting structure composite catalyst has the characteristics of large active specific surface area, multiple active sites and a regular and orderly three-dimensional multi-level structure, and exhibits excellent electrocatalytic activity and stability for OER in seawater medium.

[0064] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a composite catalyst, characterized in that: Includes steps: Step 1, providing a solution A containing a first type of transition metal salt, a solution B containing an organic ligand, a solution D containing a second type of transition metal salt, and a solution E containing sodium borohydride and a soluble base; adding the solution A to the solution B to obtain a solution C; In the solution A, the concentration of the first transition metal salt is 0.03-0.1 mol / L; in the solution B, the concentration of the organic ligand is 0.2-0.8 mol / L; in the solution D, the second transition metal salt is selected from a mixture of iron salt and tungsten salt, and the total concentration of the iron salt and tungsten salt is 0.1-0.3 mol / L; in the solution E, the concentration of sodium borohydride is 0.25-0.5 mol / L, and the concentration of the soluble base is 0.05-0.2 mol / L; Step 2: immersing the self-supporting substrate in the solution C, standing for a first preset time, and then annealing to prepare a transition metal oxide on the self-supporting substrate; the self-supporting substrate is selected from at least one of foamed nickel, carbon cloth, and foamed copper; Step 3, immersing the self-supporting substrate having a transition metal oxide on its surface into the solution D, and leaving it to stand for a second preset time; Step 4: immersing the product obtained in step 3 into the solution E and leaving it to stand for a third preset time; Step 5: Repeat steps 3 to 4 several times to prepare boron-doped transition metal oxyhydroxide on the surface of the transition metal oxide to obtain the composite catalyst; The transition metal in the first type of transition metal salt is selected from at least one of cobalt, nickel and iron; The organic ligand is selected from dimethylimidazole.

2. The method for preparing the composite catalyst according to claim 1, characterized in that: The soluble alkali is selected from at least one of sodium hydroxide and potassium hydroxide.

3. The method for preparing the composite catalyst according to claim 1, characterized in that: The annealing temperature is 300-500°C, the annealing time is 1-3 h, and the annealing atmosphere is air.

4. The method for preparing the composite catalyst according to claim 1, characterized in that: Repeat steps 3 to 4 3 to 12 times.

5. A composite catalyst, characterized in that: The composite catalyst is prepared by the preparation method of the composite catalyst according to any one of claims 1 to 4.

6. Use of the composite catalyst as claimed in claim 5 in producing hydrogen by electrolysis of water.